MO777: The Impact of Morphological and Haemodynamic Characteristics of Blood Vessels on the Arteriovenous Maturation. (3rd May 2022) - Gjorgjievski, Nikola; Dzekova-Vidimliski, Pavlina; Rambabova- Bushljetik, Irena; Dejanov, Petar; Gerasimovska, Vesna; Selim, Gjulsen; Stojanoska, Ana; Petronijevic, Dzvezdana; Janevski, Zoran; Severova- Andreevska, Galina; Nikolov, Igor; Spasovski, Goce
Abstract: BACKGROUND AND AIMS: Doppler Ultrasound (DUS) is a superior tool for the assessment of arteriovenous fistula (AVF) functionality. The aim of the study was to determine the association between morphological and haemodynamic characteristics of the blood vessels with AVF maturation. METHOD: The study was prospective that analysed 80 patients with chronic kidney disease (CKD) stage 4/5 and CKD stage 5 on haemodialysis (CKD5D) with newly created radio cephalic AVF. Haemodynamics and morphological evaluation of blood vessels by DUS was performed in all patients. The diameter of the cephalic vein, radial and brachial artery was measured: before creation, on the first day (24-h after creation) and at 4 weeks. The blood flow (BF) rate of AVF was calculated by DUS on day 1, at 4 and 8 weeks. The successful maturation of AVF was defined with BF ≥ 600 mL/min. RESULTS: The mean age of the patients was 59.9 ± 13.5 years, of which 46 (57.50%) were males. Successful AVF maturation at 4 weeks was 43.75% and 62.5% at 8 weeks. The results of six adjusted models in multivariate analyses showed BF rate on day 1 was a predictor for AVF maturation at 4 (P <0.001) and 8 weeks (P <0.001). The receiver operating characteristic (ROC) analyses showed that the highest sum of sensitivity and specificity for the BF on day 1 was 395 mL/min (sensitivity 0.714 and specificity 0.889) for the outcome at 4 weeks; and 344 mL/min (sensitivity 0.860 and specificity 0.867) for the outcome measured at 8 weeks. The diameter of the blood vessel was AVF significantly larger in patients with mature AVF compared with patients with non-mature AVF. Male gender was significantly associated with AVF maturation of AVF at fourth week (P < 0.001) and at eighth week (P = 0.001) compared with the female gender. CONCLUSION: Our study showed that BF rate of AVF on day 1 was a predictor for AVF maturation at 4 and 8 weeks. The diameter of blood vessels and male gender were statistically associated with AVF maturation.